2000
DOI: 10.1001/archsurg.135.11.1340
|View full text |Cite
|
Sign up to set email alerts
|

Does Laparoscopic Cholecystectomy Worsen the Prognosis of Unsuspected Gallbladder Cancer?

Abstract: Background: Several reports claim that there is a risk that laparoscopic cholecystectomy (LC) might worsen the prognosis of unsuspected gallbladder cancer. Hypothesis: Several factors rather than LC could influence prognosis. Methods: A retrospective clinicopathologic study was performed on 20 patients, 9 patients (3 men and 6 women, aged from 36 to 75 years [mean age, 62.3 years]) undergoing LC and 11 patients (2 men and 9 women, aged from 53 to 91 years [mean age, 65.3 years]) undergoing open cholecystectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
2
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 22 publications
3
58
2
3
Order By: Relevance
“…On the other hand, Ouchi et al 16 analyzed the results of a large number of gallbladder cancer cases treated by LC in Japan, and found no association between LC and a worse prognosis for gallbladder cancer. Some other recent reports also reached the same conclusions [17][18][19] . Furthermore, papers in which laparoscopic surgery was intentionally used in cases of gallbladder cancer have gradually increased 20,21 .…”
Section: Discussionsupporting
confidence: 76%
“…On the other hand, Ouchi et al 16 analyzed the results of a large number of gallbladder cancer cases treated by LC in Japan, and found no association between LC and a worse prognosis for gallbladder cancer. Some other recent reports also reached the same conclusions [17][18][19] . Furthermore, papers in which laparoscopic surgery was intentionally used in cases of gallbladder cancer have gradually increased 20,21 .…”
Section: Discussionsupporting
confidence: 76%
“…On the other hand, recently some reports show that the prognosis of patients with incidental gallbladder carcinoma is similar between those resected by laparoscopic approach and open approach [171][172][173][174]. However, in LC, the dissection plane on the liver side is within the subserosal layer.…”
Section: Cq16: What Are Considered As Unresectable Factors In Biliarymentioning
confidence: 98%
“…On the other hand, it has been reported that there was no statistically significant difference in the incidence of abdominal wall recurrences among LC versus OC versus LC converted to OC, and that surgical approach has no influence on prognosis [27,32]. Moreover, other reports have shown that the prognosis of GBC discovered incidentally after LC was no worse than that diagnosed after OC [10,12,33].…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%
“…Moreover, Sarli et al [33] reported that tumor stage and the occurrence of bile spillage were strongly correlated with prognosis, and that survival rate was not affected by whether the operation was carried out using LC or OC. The role of prophylactic excision of port sites is uncertain based on the current understanding of the biological behavior of the disease and clinical usefulness of such prophylactic excision has not been demonstrated [6,13].…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%